The Influence of Crane Productivity and Pilotage Service toward vessel waiting time at Terminal Petikemas Semarang Branch Pelabuhan Indonesia III - Yosevira Larasati Romawan; Riyadi - Riyadi; Nur - Rini (Politeknik Negeri Semarang, 2021)
The study examined the influence of crane productivity and pilotage service toward vessel waiting time. Multiple Linear Regression Analysis method was used to observe the influence. Secondary data were collected from Semarang Container Terminal and PT. Pelabuhan Indonesia III. The result of F-test showed that simultaneously independent variables influenced dependent variable. Meanwhile, T-test result showed only one independent variable influenced dependent variable; it was pilotage service with t count 2.859 with the significant value 0.008. Based on coefficient of determination test, the variables of crane productivity and pilotage service influence vessel waiting time by 27.6% and the other 72.4% influenced by the other variables. Regression model showed positive equation of pilotage service, it means if there is an increase in pilotage service, vessel waiting time will also increase. Suggestions that can be taken are to increase the number of pilot boats, upgrade port facilities, upgrade vasa and inaportnet application periodically. Further study is needed to investigate the other factors that influence vessel waiting time.